Management ownership and firm's value: An empirical analysis using panel data - Sang-Mook Lee; Keunkwan Ryu (Osaka University, Institute of Social and Economic Research (ISER), 2003)
Demsetz and Lehn (1985), Morck, Shleifer, and Vishny (1988), and McConnell and Servaes (1990) report different empirical findings regarding ownership structure and corporate profitability. In this paper, we re-estimate the relation between management ownership and firm's value after controlling for the history of management ownership as well as inter-firm differences using panel data. Further, we consider the possibility that the current ownership structure is jointly determined with the firm value, an endogeneity argument a la Demsetz (1983). We find that history of the management ownership, not its current level, matters in determining the firm value, which is consistent with information asymmetry arguments.
Keywords: C23; C81; D23; 330; convergence-of-interest; endogeneity; entrenchment; firm value; information asymmetry; insider ownership; panel data; Eigentümerstruktur; Management; Rentabilität; Schätzung; Unternehmenswert